Dynamic technological capability (DTC) model for the next generation of technology evolution - Bhutto, Arabella (2008)
The central question of this thesis is how should the managers and technologists of technological organisations decide on how to invest in the co-evolution of technologies and adapt their influences to the evolution of their organisational capabilities by knowing the benefits, opportunities, costs and risks of such an investment? In the context of this research the main drivers are recognized as: